2015
DOI: 10.1111/ajt.13052
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as Induction Therapy After Renal Transplantation: A Randomized, Double-Blind, Placebo-Controlled Study of Efficacy and Safety

Abstract: We evaluated the efficacy and safety of rituximab as induction therapy in renal transplant patients. In a double‐blind, placebo‐controlled study, 280 adult renal transplant patients were randomized between a single dose of rituximab (375 mg/m2) or placebo during transplant surgery. Patients were stratified according to panel‐reactive antibody (PRA) value and rank number of transplantation. Maintenance immunosuppression consisted of tacrolimus, mycophenolate mofetil and steroids. The primary endpoint was the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 33 publications
(39 reference statements)
2
49
0
3
Order By: Relevance
“…Previous reports suggested that B cell-related cytokines might play a role in late-onset neutropenia [18,19]. It was also reported that treatment with rituximab in kidney transplantation was associated with a significantly higher cumulative incidence of neutropenia [20]. However, the higher incidence of neutropenia in recipients receiving rituximab did not lead to more infections, which is in accordance with the results of other studies [21].…”
Section: Discussionsupporting
confidence: 87%
“…Previous reports suggested that B cell-related cytokines might play a role in late-onset neutropenia [18,19]. It was also reported that treatment with rituximab in kidney transplantation was associated with a significantly higher cumulative incidence of neutropenia [20]. However, the higher incidence of neutropenia in recipients receiving rituximab did not lead to more infections, which is in accordance with the results of other studies [21].…”
Section: Discussionsupporting
confidence: 87%
“…В группу повышенного иммунологического риска вошли пациенты с уровнем предсуществу-ющих антител более 6% и/или перенесшие транс-плантацию почки в анамнезе. Результаты показали достоверно большую частоту отторжений в груп-пе пациентов высокого иммунологического риска, получавших плацебо (38%), по сравнению с тремя остальными группами, где частота отторжений со-ставила 16-18% [84].…”
Section: индукция иммуносупрессииunclassified
“…41 van den Hoogen and associates conducted a randomized controlled trial to assess the efficacy of rituximab as an induction agent in both low-and highrisk kidney transplant recipients. 42 In this study, a PRA of > 6% or retransplant were considered as factors indicating high immunologic risk. Patients were randomized to either a single dose of 375 mg/m 2 of rituximab (n = 138) or placebo (n = 142).…”
Section: Rituximab Bortezomib and Eculizumabmentioning
confidence: 99%